2007
DOI: 10.1124/jpet.107.123679
|View full text |Cite
|
Sign up to set email alerts
|

Reparixin, an Inhibitor of CXCR2 Function, Attenuates Inflammatory Responses and Promotes Recovery of Function after Traumatic Lesion to the Spinal Cord

Abstract: It has been shown that the blockade of CXCR1 and CXCR2 receptors prevents ischemia/reperfusion damage in several types of vascular beds. Reparixin is a recently described inhibitor of human CXCR1/R2 and rat CXCR2 receptor activation. We applied reparixin in rats following traumatic spinal cord injury and determined therapeutic temporal and dosages windows. Treatment with reparixin significantly counteracts secondary degeneration by reducing oligodendrocyte apoptosis, migration to the injury site of neutrophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
(54 reference statements)
3
44
0
1
Order By: Relevance
“…Our results expand upon a 7-day regimen of Reparixin treatment of rats that also demonstrated improved motor function and reduced inflammation after SCI. 7 We report the novel finding that Reparixin treatment reduced the expression of Fas and p75 in the SCI lesion to levels comparable to uninjured spinal cord (Figures 3a and b). Both Fas and p75 receptors are implicated in apoptosis and contain intracytoplasmic death domains that activate caspases after SCI.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Our results expand upon a 7-day regimen of Reparixin treatment of rats that also demonstrated improved motor function and reduced inflammation after SCI. 7 We report the novel finding that Reparixin treatment reduced the expression of Fas and p75 in the SCI lesion to levels comparable to uninjured spinal cord (Figures 3a and b). Both Fas and p75 receptors are implicated in apoptosis and contain intracytoplasmic death domains that activate caspases after SCI.…”
Section: Discussionmentioning
confidence: 58%
“…5,15 Previously, neutralization of the Fas receptor ligand by antibody 6 or by soluble Fas receptor infusion 5 has been shown to reduce apoptosis, promote regeneration and improve neurological recovery after dorsal column transection or spinal cord clip-compression, respectively. Although the mechanism Reparixin diminished the expression of Fas and p75 receptors is unknown, the inhibited oligodendrocyte apoptosis and preservation of the white matter around the SCI lesion 7 could be attributed to reduced levels of Fas and p75. In this paper, we also observed that Reparixin treatment reduced the area of the spinal cord lesion, but also report a neuroprotective benefit as neurons were more abundant near the SCI lesion of Reparixin-treated rats, compared with saline-treated rats (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations